Kualitas Stik dengan Substitusi Ubi Jalar Putih - Putri, Farhani Amini; Holinesti, Rahmi; Gusnita, Wiwik; Andriani, Cici (Lembaga Yasin AlSys, 2025)
This study is motivated by the innovation effort of producing stick snacks using local ingredients, specifically steamed white sweet potatoes as a substitute for potatoes. The purpose of this research is to analyze the effect of 100% substitution with steamed white sweet potatoes on the quality of stick snacks. The study was conducted at the Culinary Arts Workshop in February 2025 using a true experimental method. The research design consisted of two treatments with three repetitions each. An organoleptic test was carried out by 15 semi trained panelists, namely IKK students who had completed the Indonesian cakes and beverages course. Data analysis was conducted using a t test to determine the significance of differences between treatments. Test results were tabulated and analyzed to assess whether the substitution significantly affected the quality of the stick snacks. The findings indicate that in terms of shape and color, both treatments produced uniformly shaped 9 cm sticks with a golden yellow hue. For the aroma aspect, treatment X2 received the highest average score of 3.07, while for texture, the highest average score of 3.62 was obtained from treatment X1. In the taste category, the highest score was again achieved by treatment X2 with an average score of 3.04. These results suggest that steamed white sweet potato substitution affects the quality of the stick snacks, particularly in the aroma and taste categories. This study recommends the use of white sweet potatoes as a potential alternative raw material in the development of local food products.